Sheikh Abdul Wahid: Strategy and Contribution to the Establishment of the Sultanate of Buton in the 16th Century - Nuraeni M; Haslinda (Sao Literasi Publisher, Yayasan Pendidikan Khaerul Munif, 2022)
The propagation of Islam by Sheikh Abdul Wahid in the kingdom of Buton had the same peculiarity as the spread of Islam in other regions, namely the use of magic. This paper is a historical analysis of Sheikh Abdul Wahid's Islamization of the Kingdom of Buton in the sixteenth century AD. This researcher employs the historical research method's four phases: heuristics, source critique, interpretation, and historiography. The findings indicated that Islamization of the Buton Kingdom began in the sixteenth century AD. This process of Islamization occurred fast and without conflict because the Sufi priests who carried out Islamization in the kingdom of Buton were neither radical nor heroic. Rather, their goal was to inculcate the Islamic faith in society. button. The acceptance of Islam in the kingdom of Buton followed a top-down model, with the elite class accepting Islam first, followed by the development and acceptance of Islam by the lower classes of society.